THE EFFECTS OF THE COVID-19 PANDEMIC ON STUDENTS IN JORDANIAN SCHOOLS: A QUALITATIVE STUDY - Huda A. Alhajjaj (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The situation in general education in the country has changed since spring semester of 2020. The purpose of this article is to explore theimpact of covid-19 on schools and education in Jordan during the lockdown. This articleexamines how coronavirus affect the students in Jordanian schools in all stages. This qualitative study utilized a case study design to explore the impact of covid-19 on schools in Jordan from the perspective of their parents. Interviews were conducted using a semi-structured discussion guide with a purposive sample of eight parents who have children in schools. The data was tape recorded and transcribed. Open coding was utilized with NVivo software. This study concluded that transition from the traditional to the online education systems at the school has many challenges for the students and their families. These challenges and difficulties including social, economic, and psychological.In the field of education, it has also been greatly affected, because in order to stop the spread of Covid-19, all students and teachers are learning from home, which is suddenly done without any preparation.